2022
DOI: 10.1111/odi.14409
|View full text |Cite
|
Sign up to set email alerts
|

Lycium barbarum polysaccharide‐glycoprotein promotes osteogenesis in hPDLSCs via ERK activation

Abstract: ObjectiveA lack of relevant research on Lycium barbarum polysaccharide‐glycoprotein (LBP) application in oral diseases. Here, we focused on the effect of LBP on osteogenic differentiation of human periodontal ligament stem cells (hPDLSCs) and periodontitis bone loss.MethodsHuman periodontal ligament stem cells (hPDLSCs) were isolated and identified by flow cytometry. Alkaline phosphatase (ALP) activity, Alizarin Red staining, and combined qPCR and Western blot analyses were performed to elucidate the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…The study also showed a reduction in alveolar bone resorption and confirmed the positive effect of L. barbarum for managing periodontitis. 65 Hence based on our results and existing evidence, it can be stated that goji berry has a promising role inmanaging periodontitis. However, one should also note that the present study evaluated the role of goji berry for only a short recall time for one month and prolonged exposure to chlorhexidine mouthwash was avoided to prevent side effects.…”
Section: Discussionsupporting
confidence: 52%
“…The study also showed a reduction in alveolar bone resorption and confirmed the positive effect of L. barbarum for managing periodontitis. 65 Hence based on our results and existing evidence, it can be stated that goji berry has a promising role inmanaging periodontitis. However, one should also note that the present study evaluated the role of goji berry for only a short recall time for one month and prolonged exposure to chlorhexidine mouthwash was avoided to prevent side effects.…”
Section: Discussionsupporting
confidence: 52%
“…Numerous studies have employed hPDLSCs in both in vivo and in vitro repair and regeneration experiments, demonstrating their effectiveness in promoting osteogenesis (24)(25)(26). However, the complexity of material construction has hindered their widespread adoption.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there has been no data in the literature comparing salivary Thy‐1 in periodontitis and obesity. Thy‐1, also known as CD90, is expressed on fibroblasts, rodent thymocytes, and T cells (Rege & Hagood, 2006), and various types of MSCs including bone marrow, periodontal ligament, adipose tissue, lung, liver, placenta, spleen (Calloni et al, 2013; Lai et al, 2022; Ying & Zhang, 2023), and inflamed tissue (Liao et al, 2011). Thy‐1 is evidenced in parotid, labial, and minor salivary glands (Andreadis et al, 2014; Togarrati et al, 2018; Wang et al, 2017; Yi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%